Unearthing the Customary Law Foundations of “Forced Marriages” During Sierra Leone’s Civil War: The Possible Impact of International Criminal Law on Customary Marriage and Women’s Rights in Post-Conflict Sierra Leone - Bélair, Karine (Columbia Journal of Gender and Law, 2006)
During the civil war that ravaged Sierra Leone from 1990 to 2001, thousands of women and girls were raped, abducted, and taken to Revolutionary United Front (RUF), West Side Boys, or Armed Forces Revolutionary Council (AFRC) rebel camps. They were assigned to a man and, from that day forward, had to submit to him sexually and perform countless domestic tasks for him. This relationship between the rebels and their captives was commonly known as “forced marriage,” with the captive women testifying that they were assigned to a “husband” or “rebel husband,” and the rebel men referring to their captives as “wives” or “bush wives.” The type of marriage that was thought to have disappeared with the conclusion of inter-tribal wars and the abolition of slavery appeared to have returned to Sierra Leone from its past, invigorated and with new force. In their articles about the conflict, reporters used the terms “wife,” “husband,” and “marriage” in quotation marks. Quotation marks were also consistently used for those terms by investigators who reported on the “forced marriage” phenomenon occurring in different armed conflicts, clearly indicating their uneasiness, if not disbelief, in the appropriate use of familial labels to describe these relationships. In fact, these reporters stated on numerous occasions that the use of such matrimonial terminology to refer to the type of situation suffered by Sierra Leonean women was inappropriate: “[d]escribing this experience as a ‘forced’ marriage is a complete misrepresentation and distortion of a [girl’s] experience”; “[t]he arrangement was sometimes referred to as ‘forced marriages’ and the women held as ‘wives,’ but these terms obfuscate the total lack of consent by the women and the coercive conditions under which they were held.” This Article will explore the use (and misuse) of the word “marriage” to describe the relationship between rebels and their captured “wives,” as well as its potential impact on the customary law of marriage. Part I sets forth the argument that the term “marriage” is a criminal misnomer that masked what, under international criminal law, was clearly a situation of sexual slavery. Part II examines the customary law of marriage in Sierra Leone to help explain why the word “marriage” may have been considered an appropriate label to describe the rebel-captive relationship. It uncovers the similarities between “forced marriages” and marriages under customary law, most significantly the possibility that sexual slavery may occur within customary law marriages.